Beyond the Battlefields of Memory: Historical Traumas and Hungarian Literature - Kisantal, Tamás (Porównania, 2020)
One can describe the contemporary Hungarian collective memory as an interpretational field of some traumatic historical events of the twentieth century. The essay aims to sketch some important tendencies of the literary representation of these events after the millennium. At first, it outlines the wider social and political contexts of these literary works. Secondly, it models the current Hungarian cultural field as an opposition between two strategies of memory labeling them in Michael Rothberg’s terminology as competitive and multidirectional ones. These approaches to the past are also associated with different ideological implications and literary canons. Finally, with a brief overview of some recent novels, the essay demonstrates some pathways of representing multidirectional attitudes to the past in the Hungarian literary fiction of the 2000s.